2005
DOI: 10.1246/bcsj.78.859
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Vitamin B12. Part 20: Supernucleophilicity of Co(I) Heptamethyl Cobyrinate toward Various Organic Halides

Abstract: Heptamethyl cobyrinate, hydrophobic vitamin B12, was reduced to its Co(I) species by a reaction with sodium tetrahydroborate, which reacted with various organic halides, such as CH2Cl2, CHCl3, CCl4, CHBrCl2, CHBr3, CCl3CH3, CFCl3, and BrCH2CH2CH3, to form the corresponding alkylated complexes with dehalogenation. The alkylated complexes were characterized by elemental analyses and ESI-MS, and the photo-lability of the alkylated complexes was confirmed by the UV–vis absorption spectral change. The fashion for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Among the coenzymes, Co(III) shows the fastest dechlorination kinetics of PCE and TCE with titanium(III) citrate [19]. Reduced cobalamin species (cobalamin(II) (Co(II)) and cobalamin(I) (Co(I))) have played the important role to shuttle electrons between diverse solid reductant surfaces and chlorinated organics [20][21][22]. Laboratory study demonstrated that redox couple (Co(II)/Co(I)) significantly transformed toxic products of PCE to non-toxic products, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Among the coenzymes, Co(III) shows the fastest dechlorination kinetics of PCE and TCE with titanium(III) citrate [19]. Reduced cobalamin species (cobalamin(II) (Co(II)) and cobalamin(I) (Co(I))) have played the important role to shuttle electrons between diverse solid reductant surfaces and chlorinated organics [20][21][22]. Laboratory study demonstrated that redox couple (Co(II)/Co(I)) significantly transformed toxic products of PCE to non-toxic products, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the electrochemical dechlorination of organic chlorides by the B 12 complex, heptamethyl cobyrinate. The Co(I) species of the B 12 complex reacts with various organic halides, such as CCl 4 , CHCl 3 , CH 2 Cl 2 , CHBr 3 , CFCl 3 (CFC‐11), and CH 3 CCl 3 , by dechlorination to form the corresponding alkylated complexes [34] . Therefore, heptamethyl cobyrinate should work as a good dechlorination catalyst.…”
Section: Electroorganic Reactions Catalyzed By B12 Complexmentioning
confidence: 99%
“…B 12s is recognized as a powerful nucleophile. Using the reactivity of the B 12 , a variety of molecular transformations was achieved, not only the B 12 ‐mimicking reactions, but also the biology‐inspired reactions, such as cyclopropane ring cleavage, reduction of a variety of substrates, including nitrite, nitrate, hydroxylamine, oxyhalogens, organic disulfides, unsaturated esters, thiosulfate, and sulfite, reductive radical cyclization, photoreduction of CO 2 , CH‐alkylation of terminal olefins, and reductive dehalogenation of organic halides . To perform these reactions, the method for generating reactive Co I species during the reaction is important.…”
Section: B12‐dependent Enzymesmentioning
confidence: 99%
“…Whereas such chemical reductants are powerful and useful for the generation of Co I , more molar equivalents of the reductant are required for the reaction and chemical waste is formed after the reaction . To alleviate this problem, the combined use of a photosensitizer with a metal complex catalyst has been developed.…”
Section: Titanium Oxide–b12 Hybrid Systemmentioning
confidence: 99%